Hydrophilic polymer vasculopathy with coinciding pseudoxanthoma elasticum‐like changes in an amputated toe. (2nd February 2017) - Gottesman, Silvija P.; Yousefi, Elham; Gupta, Raavi
Abstract : For the past decades, hydrophilic polymer gel coating have been widely used on endovascular devices to decrease friction and to aid with binding and delivering of medications in drug‐eluting stents. In the recent years, hydrophilic polymer emboli disease has been recognized as an iatrogenic adverse effect which has led to considerable morbidity and mortality of patients. This under‐recognized embolic phenomenon now has reproducible pathognomonic histologic findings. Small‐ to medium‐sized blood vessels are occluded with basophilic, amorphous, non‐refractile, non‐polarizable and whirled aggregates of foreign body material. Depending on the affected organ, the patients have variable symptomatology, from livedo racemosa, gangrene of extremities to cardiac arrhythmias, hemiparesis, stroke and death. Here, we present a unique case of hydrophilic polymer vasculopathy 6 years post‐endovascular procedure with coinciding pseudoxanthoma elasticum‐like changes. As the literature has seen increased reporting of individual cases and case series documenting the patients' diverse symptomatology; hydrophilic polymer vasculopathy should be entertained sooner in the patient's differential diagnosis.